Effortless Attendance Recording with MyOnTime: A Modern Approach for Educational Institutions - Muh Dliyaul Haq (Jurnal Penelitian Pendidikan IPA, 2023)
This study introduces MyOnTime, an innovative application designed to revolutionize student attendance management at Sekolah Indonesia Kota Kinabalu (SIKK) in response to the evolving educational landscape in the aftermath of the COVID-19 pandemic. The primary objective of this research was to develop an efficient and user-friendly solution that enhances attendance recording, promotes administrative efficiency, and aligns with current health and environmental guidelines. To achieve this goal, we employed the Extreme Programming (XP) and harnessed the AppSheet platform, a low-code application development tool. MyOnTime offers a streamlined approach to attendance recording through barcode scanning, minimizing manual data entry and reducing reliance on paper-based methods. We conducted a comprehensive user survey to evaluate the application's functionality, responsiveness, and reliability. The results indicate overwhelmingly positive user feedback, highlighting MyOnTime's effectiveness and its ability to meet the specific needs of students, teachers, and administrative staff. MyOnTime empowers educational institutions by providing real-time attendance data, comprehensive reporting capabilities, and a user-friendly interface. It supports sustainable practices by reducing paper waste and contributes to a more organized and disciplined learning environment. MyOnTime represents a promising tool for enhancing the educational experience in the post-pandemic era, promoting efficiency, convenience, and environmental friendliness in attendance management.